Hadith of Aisha’s marriage to Prophet Muhammad : an Islamic discourse on child marriage - Mohd Al Adib Samuri,; Muhammad Al-Ghazalli Abdol Malek,; Muhammad Nazir Alias,; Hopkins, Peter (Penerbit Universiti Kebangsaan Malaysia, 2022)
Child marriage is a global issue that concerns the violation of children's rights. All signatory countries to the International Convention on the Rights of the Child (UNCRC), including Malaysia, are obliged to raise the marriageable age to 18 years old as a legal measure to curb child marriage. However, the proposed law reform received strong rejection and criticism from religious groups in various Muslim countries. Religious traditionalist groups saw child marriage as permissible in Islamic law following the authority of the hadith of Aisha's marriage to Prophet Muhammad at the age of six. This article aims to analyse the abovementioned hadith by highlighting the discussion between the conflicting groups of Muslim scholars in the context of child marriage. This study employed content analysis to the Islamic legal texts and hadith commentaries in classical and contemporary works. This study found that the controversial hadith in question is a sound authority and cannot be dismissed as a legal basis for several matters in Islamic family law, including the permissibility of a father to marry off his young child. However, the hadith should not be considered as an authority to condone child marriage in today’s context. As a way forward, child rights’ advocates may pose other arguments within the Islamic law framework such as maslaha and Siyasah Shar'iyya to curb child marriage in Malaysia.